Community-based education program in Afghanistan: A study of policy and quality of education - Kayen, Hazrat Shah; Madhakomala, R. Madhakomala; Rahmawati, Desi (UIN Raden Mas Said Surakarta, 2025)
Afghanistan continues to grapple with profound challenges in delivering equitable and high-quality education, particularly in marginalized regions, despite concerted efforts to enhance educational access. This qualitative study investigates the policy frameworks and educational quality of community-based education (CBE) programs in two provinces, Nangarhar and Laghman. CBE initiatives are pivotal in mitigating barriers to education in areas beset by enduring sociopolitical adversities. Employing in-depth semi-structured interviews with nine participants—three community leaders, three directors of organizations implementing CBE, and three educators—in conjunction with a rigorous policy analysis, this study evaluates the efficacy and implementation of these programs. The findings emphasize that while CBE initiatives have markedly increased enrollment rates and bolstered community engagement, significant disparities persist in the quality of education and the execution of policy directives. Key determinants such as local governance structures, resource distribution, and cultural attitudes toward education profoundly influence these outcomes. Furthermore, challenges surrounding teacher qualifications, learning environments, and integration with the national education system remain critical concerns. This study culminates in a set of strategic recommendations aimed at refining policy frameworks and enhancing program management to address these deficiencies and advance educational outcomes.